2007
DOI: 10.1111/j.1365-2052.2007.01634.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci controlling tick [Riphicephalus (Boophilus) microplus] resistance on bovine chromosomes 5, 7 and 14

Abstract: Differences in domestication and selection processes have contributed to considerable phenotypic and genotypic differences between Bos taurus and Bos indicus cattle breeds. Of particular interest in tropical and subtropical production environments are those genetic differences between subspecies that underlie the phenotypic extremes in tolerance and susceptibility to parasite infection. In general, B. taurus cattle are more susceptible to ectoparasites than B. indicus cattle in tropical environments, and much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 30 publications
0
36
0
5
Order By: Relevance
“…[43] genotyped selected chromosomes and detected tick resistance QTL on BTA5, 7 and 14 using this same Embrapa F2 population. These results were based on preliminary phenotypic data of 300 F2 animals and included putative QTL with higher threshold (p < 0.1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[43] genotyped selected chromosomes and detected tick resistance QTL on BTA5, 7 and 14 using this same Embrapa F2 population. These results were based on preliminary phenotypic data of 300 F2 animals and included putative QTL with higher threshold (p < 0.1).…”
Section: Resultsmentioning
confidence: 99%
“…We detected various putative QTL (p < 0.05) and some of them were the ones previously reported by Gasparin et al . [43] and Regitano et al . [44] (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Although contradictory results were reported on this issue, the coat type, hair density and skin secretions may have some roles. Contemporary group comparison reveals lighter colored animals are more resistant than dark colored ones (Gasparin et al 2007). Utech et al (1978) and Silva et al (2010) observed that females, pregnant cows and younger animals are more resistant when compare to their respective counterparts.…”
Section: Expression Of Host: Resistance To Ticksmentioning
confidence: 99%
“…Consequently there remains no firm evidence of a role for any specific allele or haplotype of any of the genes in the MHC. More recently, in a linkage analysis, quantitative trait loci (QTL) were detected when a crossbred population (F2 Holstein 9 Gir) was scanned using 180 microsatellites covering all autosomal chromosomes (Gasparin et al 2007;Regitano et al 2008;Machado et al 2010a). Different QTL were found to have significant effects on tick burden in different seasons, perhaps indicating the environmental influence on tick counts.…”
Section: Gene and Markers Associated With Tick Resistancementioning
confidence: 99%
“…Non-chemical alternative methods include the use of genetically resistant animals (GASPARIN et al, 2007), the management of pastures, as well as the adoption of both biological (FRAZZON et al, 2000;BENJAMIN et al, 2002;FERNANDES et al, 2004;BASSO et al, 2005;BAHIENSE et al, 2006;LEEMON et al, 2008) and of immunologic control strategies. However, in these alternative methods, knowledge of bovine immunology, for instance the characterization of cutaneous hypersensitivity in tick susceptible/resistant bovines (BECHARA et al, 2000); of the modulation of immune responses by parasite components (KASHINO et al, 2005) or intensity of tick infestation (CRUZ et al, 2008); of the influence of host genotypic composition in the induction of an immune response (CARVALHO et al, 2008), as well as the dynamics of the tick populations (EVANS et al, 2000;MARTINS et al, 2002) that occur in each region, are all equally fundamental factors for the success of control programs.…”
Section: Introductionmentioning
confidence: 99%